Uso do bivalve límnico Anodontites tenebricosus (LEA, 1834) no biomonitoramento de metais do Rio Ribeira de Iguape - Rodrigues, Valéria Guimarães Silvestre; Fujikawa, Aline [UNESP]; Abessa, Denis Moledo de Souza [UNESP]; Hortellani, Marcos Antonio; Sarkis, Jorge Eduardo Souza; Sígolo, Joel Barbujiani (Sociedade Brasileira de Química, 2012)
This study investigated the contamination of the Ribeira de Iguape River - RIR by Cd, Zn, Cr and Pb, using the bivalve Anodontites tenebricosus as a biomonitor. Metal concentrations in tissue samples were measured by HR-ICPMS. Bivalve tissues exhibited mean levels of 1.00 µg/g Cd; 152.89 µg/g Zn; 14.79 µg/g Cr and 4.40 µg/g Pb. Lead concentrations were comparable to those reported for moderately contaminated sites. The results showed that Pb is bioavailable to the bivalves, exhibiting high concentrations and exceeding both natural and reference values for human consumption. The freshwater bivalve Anodontites tenebricosus is a suitable biomonitor of contamination by metals.
Using the freshwater bivalve Anodontites tenebricosus (LEA, 1834) as a biomonitor of metals in the Ribeira de Iguape River
Keywords: contamination; Ribeira de Iguape River; Anodontites tenebricosus